PROCESS EVALUATION OF BEHAVIOUR CHANGE COMMUNICATION MATERIALS DEVELOPED AND UTILIZED FOR HIV PREVENTION BY NON-GOVERNMENTAL ORGANIZATIONS IN OYO STATE, NIGERIA (2013)
Public health education is a major strategy for controlling the spread of HIV. An important component of this strategy is the effective utilization of well-designed Behaviour Change Communication (BCC) materials. The Oyo State World Bank-assisted HIV and AIDS programme funded 40 Non-Governmental Organizations (NGOs) from 2006 to 2008, to produce BCC materials to reach target audiences. However, the process evaluation of the development of the materials in line with the WHO model has not been systematically conducted. This study was therefore designed to assess the level of adherence by these NGOs to basic standards in the process of development of the BCC materials. The study was a descriptive cross-sectional survey. Balloting was used to select 20 out of the 40 funded NGOs. The NGOs were categorized into five equal groups based on target audience that is; Female Sex Workers, Mission Birth Attendants, In-school Youth, Women and People Living with HIV. A checklist was used to assess compliance with each of the following seven stages of educational materials development in line with the WHO model: Needs Assessment (NA); message conceptualization; design; pre-testing; production procedure; implementation and outcome evaluation. In-depth Interviews (IDIs) were conducted for the twenty NGO project coordinators while one Focus Group Discussion (FGD) was conducted among each of the five target groups. Descrptive statistics was used to analyze quantitative data while the FGD and IDI data were transcribed and analyzed using thematic approach. Only two out of twenty NGOs complied with all the seven stages of WHO model of BCC material development. All the NGOs conducted NA and material design, 95.0% carried out implementation involving target audience and 85.0% conducted outcome evaluation of the materials. Eighty percent pre-tested their materials, 65.0% conceptualized communication messages while 25.0% of the NGOs involved target audience in the production procedure. Some (40.0%) project coordinators had one form of training or the other on BCC material development while 60.0% had no training. Only 35.0% conducted training for their target audiences before distributing the materials. Weak technical capacity in BCC material development was a major challenge as reported by the project coordinators. The FGD findings corroborated responses from the IDIs that target audiences were involved in NA, pre-testing and material distribution but not in message conceptualisation, production procedure and outcome evaluation. Adherence to basic standard process of developing Behaviour Change Communication material is low among the Non-Governmental Organizations assessed. An intervention comprising training and supportive supervision is needed to enhance the skills of project coordinators in the development of behavioural change communication materials.